Genome-wide identification and analysis of CKX genes in Poncirus trifoliata. Issue 6 (1st November 2016) - Ma, Yan-yan; Zheng, Li; Xie, Rangjin; He, Shao-lan; Deng, Lie
ABSTRACT: Cytokinin oxidase/dehydrogenases (CKXs) in plants are coded by a small multigene family and play important roles in maintaining cytokinin homeostasis. In this study, four CKX genes (i.e. PsCKX1, PsCKX2, PsCKX5, and PsCKX7 ) were cloned from Poncirus trifoliata . All PsCKXs contained a highly conserved flavin adenine dinucleotide (FAD) binding domain and a cytokinin dehydrogenase 1, FAD/cytokinin binding domain. PsCKX1 and PsCKX2 shared 66.2% and 65.4% identity with AtCKX6 and AtCKX1, respectively, while PsCKX5 and PsCKX7 exhibited less than 45% identity with AtCKXs. The expression analysis under abiotic conditions (NaCl, ABA, 6-BA and drought) revealed that the four PsCKX genes could respond to at least one treatment, and the expression patterns were diverse in root and leaf. Overexpressing four PsCKX genes in tobacco led to diverse phenotypic variations in transgenic plant, including leaf shape, root architecture, and plant height. In addition, the data showed that PsCKX2 and PsCKX5 hold promise to obtain citrus dwarf rootstock with a stronger root system, since the overexpression of them resulted in dwarf plants with more lateral roots. Taken together, the work lays the basis for applications of PsCKX genes in future.